Maternal and neonatal 25‐hydroxyvitamin D concentrations and school‐age lung function, asthma and allergy. The Generation R Study. Issue 6 (29th April 2019) - Mensink‐Bout, Sara M.; van Meel, Evelien R.; de Jongste, Johan C.; Voortman, Trudy; Reiss, Irwin K.; De Jong, Nicolette W.; Jaddoe, Vincent W. V.; Duijts, Liesbeth
Summary: Background: Vitamin D deficiency in early life might affect the developing lung and immune system, and subsequently influence the risk of asthma and allergy in later life. Objective: We examined the associations of 25‐hydroxyvitamin D concentrations in mid‐gestation and at birth with lung function, asthma, inhalant allergic sensitization and inhalant allergy at school‐age. Methods: This study among 4951 children and their mothers was embedded in a population‐based prospective cohort in Rotterdam, the Netherlands. Maternal venous blood samples in mid‐gestation and umbilical cord blood samples at birth were used to determine 25‐hydroxyvitamin D concentrations. At age 10 years, lung function was measured by spirometry, current asthma and physician‐diagnosed inhalant allergy by questionnaire, and inhalant allergic sensitization by skin prick tests. We used multivariable regression models to examine associations. Results: Higher 25‐hydroxyvitamin D concentrations in mid‐gestation were associated with a higher forced vital capacity (FVC), but a lower forced expiratory volume in 1 second/FVC (FEV1 /FVC) and a lower forced expiratory flow after exhaling 75% of FVC (FEF75 ) ( Z ‐score differences [95% CI] 0.02 [0.00, 0.03], −0.02 [−0.03, −0.01] and −0.01 [‐0.03, −0.00], respectively, per 10 nmol/L 25‐hydroxyvitamin D), but not with asthma. Furthermore, higher 25‐hydroxyvitamin D concentrations in mid‐gestation were associated with an increased risk of inhalant allergy (Odds Ratio [95% CI] 1.07 [1.02, 1.12]), but not with inhalant allergic sensitization. After additional adjustment for child's 25‐hydroxyvitamin D concentrations at the age of 6 years, only the associations of 25‐hydroxyvitamin D concentrations in mid‐gestation with FEV1 /FVC and FEF75 remained. We did not find consistent associations of 25‐hydroxyvitamin D concentrations at birth with respiratory or allergy outcomes. Conclusion and clinical relevance: Our results suggest that maternal 25‐hydroxyvitamin D concentrations in mid‐gestation may influence lung development. The clinical implications of the observed associations remain unclear.